2016
DOI: 10.3389/fvets.2016.00098
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of Dairy Cows Does Not Limit the Behavioral Response to Treatment in Mixed Treatment Experimental Designs

Abstract: In many research studies, animals assigned to different treatments are housed adjacently or together in a group. One critique of these designs has been the potential role of behavioral facilitation and synchronization between animals on different treatments in mixed treatment groups (heterogeneous groups). To evaluate this, we compared the synchrony of feeding behavior between dairy cows housed in heterogeneous groups to cows exposed to the same treatment simultaneously (homogenous groups). Twenty-four cows we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It could be suggested that housing cows on different treatments within the same pen can influence their feeding behavior through social facilitation (Hart et al, 2013), and that cows in the current study on the high-frequency treatment could have altered the behavior of cows on the low-frequency treatment, resulting in the lack of observed differences. However, King et al (2016a) found that when working with mixed treatment groups, synchrony of feeding behavior of cows on the same treatment was much greater than synchrony of a cow with those on a different treatment. Those researchers concluded from their results that the behavioral response to a specific treatment is driven by the treatment they are on more than by the behavior of neighboring cows on a different treatment.…”
Section: Discussionmentioning
confidence: 95%
“…It could be suggested that housing cows on different treatments within the same pen can influence their feeding behavior through social facilitation (Hart et al, 2013), and that cows in the current study on the high-frequency treatment could have altered the behavior of cows on the low-frequency treatment, resulting in the lack of observed differences. However, King et al (2016a) found that when working with mixed treatment groups, synchrony of feeding behavior of cows on the same treatment was much greater than synchrony of a cow with those on a different treatment. Those researchers concluded from their results that the behavioral response to a specific treatment is driven by the treatment they are on more than by the behavior of neighboring cows on a different treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Diet assignment was balanced, within group, for parity, DIM, and production level. Treatments were assigned to alternating feed bins, leaving the LS and SS treatments adjacent to each other, to minimize synchronization of feeding behavior (King et al, 2016). In the first experimental group of 15 cows, 8 cows were on the LS treatment and 7 were on the SS, whereas in the second group of 15 cows, 8 cows were on the SS treatment and 7 were on the LS treatment.…”
Section: Experimental Designmentioning
confidence: 99%
“…Studies are as follows: (1)Hart et al, 2014; (2)Hart et al, 2013; (3) DeVries and Chevaux, 2014; (4)King et al, 2016a; and (5)King et al, 2016b. 3 PP = primiparous; MP = multiparous.4…”
mentioning
confidence: 99%